Phytochemical constituents and in vitro antioxidant capacity of Tabernaemontana catharinensis A. DC - Boligon, Aline Augusti; Freitas, Robson Borba de; Brum, Thiele Faccim de; Piana, Mariana; Belke, Bianca Vargas; Rocha, João Batista Teixeira da; Athayde, Margareth Linde (Free Radicals and Antioxidants)
Introduction: Free radicals induce numerous diseases by lipid peroxidation, protein peroxidation, and DNA damage. It has been reported that numerous plant extracts have antioxidant activities to scavenge free radicals. In this present study we determined the in vitro antioxidant capacity and quantified of total phenolics, flavonoids, tannins and alkaloids of Tabernaemontana catharinensis crude extract and fractions leaves. Methods: The antioxidant potential was evaluated by 1,1-diphenyl-2-picryl-hydrazyl free radical (DPPH) scavenging and thiobarbituric acid reactive species (TBARS) methods, total phenolics content was determined using the FolineCiocalteu assay, flavonoids, tannins and alkaloids were determined by spectrophotometer. Results: Crude extract and fractions showed inhibition against TBARS, ethyl acetate was the most effective fraction (IC50 ¼ 6.71 0.19 mg/mL), subsequently by butanolic (26.15 0.08 mg/mL), dichloromethane (43.25 0.12 mg/mL) and crude extract (61.09 0.05 mg/mL), respectively. Moreover, the DPPH assay, presented IC50 value ranged of 4.64 1.25 to 27.78 0.93 mg/mL. Contents of total phenols, flavonoids, tannins and alkaloids of T. catharinensis followed the order: ethyl acetate > butanolic > dichloromethane fractions > crude extract. Conclusion: The present study, we found that the crude extract and fractions of T. catharinensis showed good antioxidant activity. Among the samples tested, the ethyl acetate fraction showed better activity than others.
Keywords: Tabernaemontana catharinensis; Apocynaceae; Antioxidant; TBARS